A large scale self-supported WP–W2C nanoporous network for efficient hydrogen evolution reaction in alkaline media. Issue 20 (26th April 2022) - Huang, Jingwen; Jian, Chuanyong; Cai, Qian; Hong, Wenting; Liu, Wei
Abstract : A large-scale WP–W2 C heterojunction with a nanoporous structure is constructed to enhance the HER performance and corrosion stability under high pH conditions, high temperatures and large current densities that satisfy industrial requirements. Abstract : A nanoporous structure can highly expose active atomic sites and has excellent electrolyte/electrode interface mass transport characteristics, which plays an important role in the design of high-performance hydrogen evolution reaction (HER) catalysts. In this work, we fabricate a large-scale WP–W2 C electrocatalyst with a nanoporous network structure. The SEM results suggest that the introduction of the P precursor not only decreases the synthesis temperature of W2 C but also enlarges the pores of the nanoporous network appropriately. Surprisingly, the self-supported nanoporous feature with a small water contact angle provides this seamless electrode a mechanically-robust and more convenient gas transport channel, facilitating the electron transfer and the formation and release of H2 bubbles. The WP–W2 C nanoporous network presents excellent catalytic stability and activities with low overpotentials of 560 mV and 449 mV at a current density of 1000 mA cm −2 in 1.0 M KOH at 25 °C and 70 °C, respectively, and the electrode also displays outstanding HER performance in 5.0 M KOH, which satisfies the demand of the industrial application.